The Influence of UB Coffee Malang's Semi-Open Design on Visitors'Perception of Thermal Comfort - Vinka Cristhiani (Departemen Arsitektur Fakultas Teknik Universitas Brawijaya, 2023)
Comfort is one of the aspects that plays a role in supporting human activity, one of which is thermal comfort. Therefore, it is important to know visitor perceptions and the influence of UB Coffee's semi-open building design in providing thermal comfort. The space is a semi-open cafÃ© with no sufficient cooling device, so user comfort highly depends on the thermal environment condition which has high humidity. This research was conducted using quantitative methods through field measurements and distributing questionnaires. The results showed that visitors felt quite comfortable with UB Coffee's thermal conditions and semi-open design. The results also show that the wind speed has a significant effect on visitor comfort out of the other two variables, air temperature and air humidity. The semi-open design is implemented through the use different types of natural ventilation such as rosters, 2.9m wide openings for access, and hollow aluminum trellis doors. However, overall openings allow the wind flow to create natural cross-ventilation so the air circulation is maintained. Good air circulation increases evaporation so that the high humidity from the environment around UB Coffee can be reduced and creates comfort for the users.